MALAYSIAN FOREIGN POLICY ON THE ISSUE OF ICERD (INTERNATIONAL CONVENTION ON THE ELIMINATION OF ALL FORMS OF RACIAL DISCRIMINATION) - Muhammad Fatahillah (The Indonesian Islamic Studies and International Relations Association (Insiera), 2019)
ICERD (International Convention on the Elimination of All Forms of Racial Discrimination) is international treaty initiated by the United Nations to encounter racial discrimination. It was inspired by various racial discrimination in US, UK, Germany, and Spain. At 20 November 1963, some countries in UN initiated Declaration on the Elimination of All Forms of Racial Discrimination. The declaration then became ICERD at 21 December 1965 and opened to be signed at 7 March 1966. On November 2018, 179 countries had ratified ICERD. Meanwhile, 18 countries not yet ratified ICERD, including Malaysia. This article tries to find reasons of why Malaysia not yet ratified ICERD while international pressure on this issue is quite high. To answer the research problem, the writer utilize Robert D. Putnam‘s Two-Games theory. The research concluded that the government of Malaysia not yet ratified ICERD due to higher domestic political pressure rather than international.